The isolation, quantification and synthetic modification of antiplasmodial natural products from sargassum heterophyllum - Munedzimwe, Tatenda Carol (Rhodes University, Faculty of Pharmacy, Pharmacy, 2012)
Malaria is one of the most deadly parasitic diseases known to man. Although the number of malaria cases reported each year is decreasing, this disease continues to pose health and economic problems mainly in developing countries. Significant progress has been made in the fight against this disease. This includes the discovery and development of potent antimalarial agents. However, the development of resistance to most of these potent antimalarials has made the development of new antiplasmodial agents of paramount importance. Several promising antiplasmodial agents have been found from the marine environment. Amongst these are the tetraprenylated toluquinols from the brown alga: Sargassum heterophyllum. These metabolites have been reported to exhibit a range of antiplasmodial activity; however, the mechanisms by which these compounds bring about their antiplasmodial activity and the pharmacophoric groups responsible for such activity are unknown. Two species of Sargassum algae were encountered during the course of this project. From the investigation of the geographical and seasonal variation of metabolites of S. heterophyllum and S. elegans we established that there were no significant intra and inter site variations amongst metabolite profiles of both species both within and between the sampled seasons. These results enabled us to establish that the collection of both species from three different sites on the eastern coast of South Africa namely; Kenton on Sea, Port Alfred and Noordhoek in autumn, winter or spring would qualitatively yield the same metabolites. A comparison of metabolite profiles of both species also revealed no qualitative differences between metabolites of S. heterophyllum and S. elegans. The quantities of selected prenylated metabolites extracted from S. heterophyllum using four different extraction techniques was also assessed using qNMR as the method of quantification. This led to the identification of optimal extraction techniques and conditions for the extraction of sargahydroquinoic acid (1.38), sargaquinoic aid (1.39) and sargachromenol (2.10) from S. heterophyllum. From this study, the extraction of algae by soxhlet extraction using EtOH as the extraction solvent led to the extraction of the highest quantities of sargahydroquinoic acid. The potential of other extraction techniques such as microwave assisted extraction, to yield high quantities of the selected metabolites were also identified. With gram quantities of sargahydroquinoic acid (1.38) in hand, this compound was modified by oxidation, reduction, acetylation, methylation and cyclization reactions to yield nine derivatives. The derivatives and four naturally occurring prenylated toluquinols were assessed for antiplasmodial and cytotoxic activity against the FCR-3 Gambian Chloroquine resistant strain of P. falciparum and the MDA-MB-231 breast carcinoma cell line respectively. Comparison of antiplasmodial data for all twelve compounds showed that the hydroquinone moeity of sargahydroquinoic acid (1.38) is important for antiplasmodial activity while esterification of the carboxylic acid group in 1.38 resulted in more potent antiplasmodial compounds. Of all twelve compounds, compound 5.2, the hydroquinone methyl ester of 1.38 was found to be the most potent antiplasmodial compound with an ICâ‚…â‚€ value of 1.94 Î¼M and a selectivity index of 22.68.
Keywords: Malaria -- Developing countries -- Prevention; Antimalarials